Achieving Developmental and Pro-Poor Trade in Africa: the Mauritian Transition-Emerging-Economy: Success Case Study-Initiatives, Innovations and Incentives - GUNPUTH, Rajendra Parsad (Journal of Social and Development Sciences, 2014)
In a contextualized approach the author explores development achievements in terms of propoor trade in Mauritius and to its transition-economy. Indeed, Mauritius is very notorious for its aggressive economic and financial lobbying specially on the African continent coupled to its openness strategy, easy-doing business with implementation of various national and strategic policies (development of its Freeport harbours and Export Processing Zone (EPZ), offshore sectors with massive foreign direct investment (FDI), development of the BPO and ICT sector in the Cyber City, diversification of the Mauritian export from sugar to industrial goods with major development in some emerging sectors such as trade in services through the tourism industry which is now contributing up to 8% of its GDP with massive employment in its hotels and construction, and Mauritius is actually targeting to exploit its exclusive economic zone) to increase both its imports of raw materials and exports of goods. Furthermore, it is a member of various regional economic blocks in the region (COMESA, SADC, IOR) to attract African investors and to bridge China and India to the African continent. All these strategies, factors and polices including strategic importance of Mauritius have contributed to trade diversification which in turn has created jobs to combat poverty eradication in a wealthier nation so far. Data to reflect and/or to prove same are borrowed mainly from the Central Statistics Office (CSO) in Mauritius, the Board of Investment in Mauritius (BOI), UNCTAD and the Bank of Mauritius Annual Reports principally during the period 2001-2012. The paper, with facts and figures, reflects to what extent achieving developmental and poor-trade is possible on the African continent. Is the Mauritian economy a reliable model? Why is it so wealthy actually or whether its economic miracle has been a mere luck up to now?